СВОЙСТВА МЕЖГЕННЫХ miRNA ЧЕЛОВЕКА И ОСОБЕННОСТИ ИХ ВЗАИМОДЕЙСТВИЯ С mRNA (Experimental biology, 2015)
Sites of interaction of 784 intergenic miRNAs with mRNAs of 52 genes coding intronic miRNAs are established. Features of interaction of observed miRNAs with mRNAs of each gene in 5'UTR, CDS and 3'UTR are revealed
Keywords: interaction